الفحولة المُدّجنة في الرواية النسوية التونسية رواية طرشقانة لــ مسعودة أبو بكر - بن عمر, سهيلة (جامعة الوادي - University of Eloued, 2021)
ملخص: يهدف المقال إلى تسليط الضوء على قيمة الجسد الذكوري وكيفية تحوله إلى جسد أنثوي في رواية ' طرشقانة ' للروائية التونسية مسعودة أبو بكر ، التي تحاول تصوير الصراع القائم بين سلطة الخطاب الذكوري أو التمرد على هذا الخطاب وكسر مبادئه الالزامية من خلال تناول خطاب الجسد المقموع والمراهنة عليه ثقافيا وجماليا كخطاب يستحق التناول والمعالجة . ومن هذا المنطلق ، تروم هذه الورقة البحث في مفهوم الفحولة ومسار تحولاتها وتدجينها ، ومعالجة نماذج متنوعة لفضاء الجسد في الرواية النسوية المعاصرة . وعلى هذا الأساس حاولت هذه الورقة البحثية الاعتماد في معالجة هذا النص على آليات السيموطيقا ، وقضايا النقد النسوي والنقد الثقافي . الكلمات المفتاحية: الفحولة؛ الجسد ؛الجندر؛ الأنوثة ؛الذكورة؛ التدجين؛ الرواية النسوية ؛الرواية النسوية التونسية المعاصرة . Abstract: The article is aiming at shedding light on the value of the male body and how it transforms into a female body in the novel 'Tarshakana' by the Tunisian novelist Masouda Abu Bakr, who tries to portray the conflict between the authority of the male discourse or rebellion against this discourse and break its obligatory principles by addressing the discourse of the suppressed body and betting on it. Culturally and aesthetically, as a speech that deserves to be addressed and addressed. From this standpoint, this paper aims to research the concept of virility, its path of transformation and domestication, and to address various models of the body space in the contemporary feminist novel. On this basis, this research paper tried to rely in addressing this text on the mechanisms of semioticism, and issues of feminist and cultural criticism. key words:virility;The body Femininity, masculinity; Domestication; The Feminist Novel; The Contemporary Tunisian Feminist Novel.
مقال
Keywords: الجسد ; الجنس ; الجندر ; ذكر ; أنثى ; طرشقانة ; الفحل